Miguel Soler in the land of the brave. La Mina, Uruguay, 1954-1961 - García Alonso, María (Historia y Memoria de la Educación, 2018)
In 1954, one of the most innovative educational experiences of the decade took place in rural Uruguay: the First Experimental School Nucleus of La Mina. It was directed by Miguel Soler Roca, a Spanish-Uruguayan teacher who had been awarded a scholarship to study basic education in CREFAL, shortly after the creation of this organism. In 1958 Margaret J. Anstee, Representative of the UN in Uruguay, went to La Mina to interview him. She thought that it would show the keys to the success of the proposal and would explore the possibility of exporting the experience as an inspiring model in other latitudes. The present text transcribes this interview, unpublished until now, contextualizing it with other documents that explain the development of this initiative.